MADONNA AND BEYONCÉ - FROM POP MUSIC DIVAS TO FEMINIST ICONS: ANALYSIS OF FEMINISM UNDER THE MULTIMODAL BIAS AND SOCIAL SEMIOTICS - Campos Freitas , Henrique; José Alves, Ricardo (Revista (Entre Parênteses), 2023)
This article has a general objective to analyze, through the reflections of Hodge and Kress (1988), essential authors of the Social Semiotic, provide subsidies for the expansion of the possibilities of theoretical discussions beyond the written code., the representation of feminism in the songs Like a Virgin, by Madonna, and Run The World (Girls), by Beyoncé, as well as in the presentations of these singers in the most important music award, the MTV Video Music Awards. As specific objectives, we tried to understand which feminist characteristics are common and divergent both in the two songs, as in the performances of Madonna and Beyoncé, in addition to analyzing the influence of these singers on what is understood by feminism, discussing the ways in which Madonna and Beyoncé trigger different semiotic modes when dealing with the feminist movement in these songs and presentations, discussing the effects of meaning produced in the songs and presentations of the singers as mentioned earlier for the pursuit of female empowerment. With the study it was possible to highlight that, each in its own way, it manages to awaken in public, an action to fight against those who seek an increasingly patriarchal society, in which man is the center of actions.